Notice of Retraction Utilizing the ATM technology in e-distance learning - Abbas Hieder, Inaam; Mohammad Abdullah, Sara; Ahmed Ali, Rawaa (Indonesian Journal of Electrical Engineering and Computer Science, 2020)
Notice of Retraction-----------------------------------------------------------------------A duly constituted expert committee found this paper to be in violation of IAES's publication principles after carefully and thoughtfully reviewing its content.We hereby retract this paper's content. We should make a reasonable effort to remove all past references to this paper.The presenting author of this paper has the option to appeal this decision by contacting ijeecs@iaescore.com, cc: info@iaesjournal.com.-----------------------------------------------------------------------There is an Increasing demand for the education in the field of E-learning specially the higher education, and to keep contiuity between the user and the course director in any place and time. This research presents a proposed and simulation multimedia network design for distance learning utilizing ATM technique. The propsed framework determines the principle of ATM technology and shows how multimedia can be integrated within E- learning conteext. The first part of this research presents a theoretical design for the Electricity Department, university of technology. The purpose is to illustrate the usage of the ATM and Multimedia in distance learning process. In addition, this research composes two entities: Software entity by using image, sound and a mix between them to be transfered across the ATM network.. The MATLAB was used to validate the implementation of the required design objectives: (hardware entity) where a prototype is designed (experimental trial) , which aims to carry out the connectivity process between the user and course director, where multiple PCs are connected via unshielded twisted pair (UTP) and a web camera with microphone have been attached to PCs. To finalize this stage, an interface is implemented to show the data transmission process for multimedia by the ATM network and it has been realized through the Visual Basic language. Finally, to validate the level of success by using the ATM technique, some important factors have been determined through the analysis phase, which are: time delay, throughput and efficiency. The propsed design manages to minimize the impat of noise and improve the throuput ratio by 30% while minizing the delay with a ratio of 22%.